Localization of mutant ubiquitin in the brain of a transgenic mouse line with proteasomal inhibition and its validation at specific sites in Alzheimer's disease - Gentier, Romina J. G.; Verheijen, Bert M.; Zamboni, Margherita; Stroeken, Maartje M. A.; Hermes, Denise J. H. P.; Küsters, Benno; Steinbusch, Harry W. M.; Hopkins, David A.; Van Leeuwen, Fred W. (Frontiers in Neuroanatomy, 2015)
Loss of protein quality control by the ubiquitin-proteasome system (UPS) during aging is one of the processes putatively contributing to cellular stress and Alzheimer’s disease (AD) pathogenesis. Recently, pooled Genome Wide Association Studies (GWAS), pathway analysis and proteomics identified protein ubiquitination as one of the key modulators of AD. Mutations in ubiquitin B mRNA that result in UBB+1 dose-dependently cause an impaired UPS, subsequent accumulation of UBB+1 and most probably depositions of other aberrant proteins present in plaques and neurofibrillary tangles. We used specific immunohistochemical probes for a comprehensive topographic mapping of the UBB+1 distribution in the brains of transgenic mouse line 3413 overexpressing UBB+1. We also mapped the expression of UBB+1 in brain areas of AD patients selected based upon the distribution of UBB+1 in line 3413. Therefore we focused on the olfactory bulb, basal ganglia, nucleus basalis of Meynert, inferior colliculus and raphe nuclei. UBB+1 distribution was compared with established probes for pre-tangles and tangles and Aβ plaques. UBB+1 distribution found in line 3413 is partly mirrored in the AD brain. Specifically, nuclei with substantial accumulations of tangle-bearing neurons, such as the nucleus basalis of Meynert and raphe nuclei also present high densities of UBB+1 positive tangles. Line 3413 is useful for studying the contribution of proteasomal dysfunction in AD. The findings are consistent with evidence that areas outside the forebrain are also affected in AD. Line 3413 may also be predictive for other conformational diseases, including related tauopathies and polyglutamine diseases, in which UBB+1 accumulates in their cellular hallmarks.